Dynamic modulus thermal analysis on polymer composite (high density polyethylene with natural rubber) / Sharadina Embong - Embong, Sharadina (Research Management Institute (RMI), 2007)
The dynamic modulus thermal analysis on polymer composite (high density polyethylene (HDPE) with natural rubber (NR)) was ascertained. The composites containing 100% HDPE, 90% HDPE 10% NR, 80% HDPE 20% NR were produced by blending them together and pressing them into a mold shape. The testing using Perkin Elmer DMA - 7 is to get the data of mechanical properties of composition such as storage modulus, E', loss modulus, E" and damping factor, tan 8 and plot them as a function of temperature, Celsius (°C). The range of temperature used is about -150°C to 150°C and using the fixed frequency 1Hz. Many equipments and techniques can be used to find the mechanical properties of composite. However, DMTA technique can do it at wide range temperature compared to others such as DSC technique. From the graph of loss modulus and damping factor, the glass transition temperature, Tg can be obtained. The glass transition temperature is a key factor in deciding the usefulness of a polymer. The composites added with NR have higher damping ability that leads to poor molecular bonding. To get the better results, the compatibalizer can be used when adding HDPE with NR.